2018
DOI: 10.2174/1570159x15666170601125139
|View full text |Cite
|
Sign up to set email alerts
|

Potential Medications or Compounds Acting on Toll-like Receptors in Cerebral Ischemia

Abstract: Background: Toll-like receptors play an integral role in the process of inflammatory response after ischemic in-jury. The therapeutic potential acting on TLRs is worth of evaluations. The aim of this review was to introduce readers some potential medications or compounds which could alleviate the ischemic damage via TLRs.Methods: Research articles online on TLRs were reviewed. Categorizations were listed according to the follows, methods acting on TLRs directly, modulations of MyD88 or TRIF signaling pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 132 publications
1
28
0
Order By: Relevance
“…Then, LPS activates TLR4, which can initiate downstream signals via two main transduction signaling branches, myeloid differentiation factor88 (MyD88) and TIR-domain-containing adapter-inducing interferon-β (TRIF; Chattopadhyay et al, 2015 ; Wang, 2015 ). The TLR4 signaling pathway, via the two distinct branches of the MyD88- and TRIF-dependent pathways, activates the translocation of nuclear factor-kappa B (NF-κB) into the nucleus ( Khan et al, 2016 ; Singh et al, 2017 ; Li et al, 2018 ). Both of these pathways play critical roles in the expression of a series of inflammatory factors, including tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 ( Ben et al, 2012 ; Hwang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, LPS activates TLR4, which can initiate downstream signals via two main transduction signaling branches, myeloid differentiation factor88 (MyD88) and TIR-domain-containing adapter-inducing interferon-β (TRIF; Chattopadhyay et al, 2015 ; Wang, 2015 ). The TLR4 signaling pathway, via the two distinct branches of the MyD88- and TRIF-dependent pathways, activates the translocation of nuclear factor-kappa B (NF-κB) into the nucleus ( Khan et al, 2016 ; Singh et al, 2017 ; Li et al, 2018 ). Both of these pathways play critical roles in the expression of a series of inflammatory factors, including tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 ( Ben et al, 2012 ; Hwang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we employed a mouse model of MCAO to evaluate the effects of poly(I:C) preconditioning on cognitive dysfunction after cerebral I/R injury and the related mechanisms. We Recent studies have indicated that TLR-mediated signaling plays an important role in cerebral I/R injury [4,32]. TLR4 deficiency [5] or TLR2 modulation [33] protects the brain from I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…TLR9 signaling pathway, as an important hinge between innate immunity and acquired immunity, can play an immune regulatory role in the early stage of pathogen invasion [ 39 ]. In ischemic brain injury, TLR9 activates the downstream signaling molecule NF- κ B by binding to specific ligands and participates in inflammatory response [ 40 ]. Trop et al [ 41 ] found that CPB increased inflammatory response, induced high expression of interferon-gamma (INF- γ ), TNF- α , IL-6, IL-8, and IL-10, activated TLRs signaling pathway, and upregulated IRAK-4 and NF- κ B expression.…”
Section: Discussionmentioning
confidence: 99%